The Application of FTIR Spectroscopy Combined Chemometrics for Analysis of Keting Fish Oil in Binary Mixture with Patin Fish Oil and Palm Oil - Nadia Miftahul Jannah; Abdul Rohman; Lily Arsanti Lestari (Journal of Food and Pharmaceutical Sciences, 2023)
Keting fish (Mystus gulio) is a local fish from Indonesia. The quality of keting fish oil needs to be maintained to avoid counterfeiting. The use of Fourier transform infrared (FTIR) spectroscopy can be developed for quantitative analysis of keting fish oil (KFO) in binary mixtures with palm oil (PO) and patin fish oil (PFO). In this present research, PLS and PCR models were used to construct a multivariate calibration for the KFO content in the binary mixtures analyzed at fingerprint region frequencies of 1500-1000 cm-1. The results showed that PLS with second derivative FTIR spectra was well suited for quantitative analysis of KFO-PFO with a value of the coefficient of determination (R2) = 0.997 and the error expressed as root mean square error of calibration (RMSEC) = 0.0204. Meanwhile, R2 0.999 and RMSEC values obtained for KFO in a mixture with PO were and 0.0133. In general, FTIR spectroscopy serves as a suitable technique for the determination of KFO in mixtures with other oils.